Characterization of the Pseudomonas aeruginosa recA gene: the Les- phenotype. - Kokjohn, T A (1988)
The Les- phenotype (lysogeny establishment deficient) is a pleiotropic effect of the lesB908 mutation of Pseudomonas aeruginosa PAO. lesB908-containing strains are also (i) deficient in general recombination, (ii) sensitive to UV irradiation, and (iii) deficient in UV-stimulated induction of prophages. The P. aeruginosa recA-containing plasmid pKML3001 complemented each of these pleiotropic characteristics of the lesB908 mutation, supporting the hypothesis that lesB908 is an allele of the P. aeruginosa recA gene. The phenotypic effects of the lesB908 mutation may be best explained by the hypothesis that the lesB908 gene product is altered in such a way that it has lost synaptase activity but possesses intrinsic protease activity in the absence of DNA damage. The Les- phenotype is a result of the rapid destruction of newly synthesized phage repressor, resulting in lytic growth of the infecting virus. This hypothesis is consistent with the observations that increasing the number of copies of the phage repressor gene by increasing the multiplicity of infection (i.e., average number of phage genomes per cell) or by introducing the cloned phage repressor gene into a lesB908 mutant will also suppress the Les- phenotype in a phage-specific fashion.